Simple dynamic overmodulation strategy for fast torque control in DTC of induction machines with constant-switching-frequency controller - Jidin, Auzani; Nik Idris, Nik Rumzi; Mohamed Yatim, Abdul Halim; Sutikno, Tole; Elbuluk, Malik E. (IEEE, 2011)
This paper presents a simple dynamic overmodulation method to obtain a fast dynamic torque response in direct torque control (DTC) of induction machines with constant-switching-frequency controller. A fast dynamic torque response can be obtained by switching only the most optimized voltage vector during torque dynamic condition. The optimized voltage vector can be identified by comparing the rate of change of torque produced between applications of two possible active voltage vectors, according to the flux position. The selection of the optimized voltage vector can be simply implemented by modifying the flux error status before it is being fed to the lookup table. It will be shown that the proposed switching strategy facilitates the DTC to perform under six-step mode to achieve the fastest dynamic torque response. The effectiveness of the proposed dynamic overmodulation to obtain the fast torque response is verified with some experimental results.